Albanian Individual Taxpayers Perceptions and Determinants on Ethical Behavior Regarding Tax Compliance - Michael J. Salé; Oltiana Muharremi; Meleq Hoxhaj (Business Ethics and Leadership)
Tax evasion and tax avoidance are among the most addressed topics in economic literature in recent years, as one of the most discussed issues in different countries. The research’s primary purpose is to present Albanian residents’ and taxpayers’ perceptions regarding tax evasion, tax avoidance, and tax compliance. The leading indicators used in this report, the attitude towards tax evasion and tax avoidance, rely on individual taxpayers’ perceptions and not on factual evidence such as the amount of income hidden from the tax authorities. Several studies have been done in different countries regarding the population’s perception regarding factors affecting evasion. In this paper, we investigated the following logical sequence: in the beginning, we provided an overview of the fiscal system and legislation, informal economy, and fiscal evasion in Albania. This analysis data was taken from reports from national and international organizations. After this, we analyzed data obtained from a survey issued to 387 taxpayer individuals in Albania. Our objective was to identify, using empirical analysis, factors that influence an individual’s ethical perception of tax avoidance and evasion. The statistical analyses we carried out in the paper were factor analyses and ordinal logistic linear regression analyses using the JMP statistical software. Based on the empirical research, we concluded that government policies positively correlate with taxpayers’ behavior regarding tax compliance. Among other determinants influencing tax evasion, we have evaluated that higher tax rates are an essential element. The results of the research can be helpful for governments and other policymakers’ institutions.